2017
DOI: 10.1007/s00705-017-3575-y
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus A strains obtained from children with acute gastroenteritis in Mozambique, 2012-2013: G and P genotypes and phylogenetic analysis of VP7 and partial VP4 genes

Abstract: In Mozambique rotavirus (RV) was shown to be the greatest cause of acute diarrhoea in infants from 0 to 11 months, and in 2015, national rotavirus vaccination was introduced. As with other developing countries, there is very limited active strain characterisation. Rotavirus positive clinical specimens, collected between 2012 and 2013, have now provided information on the genotypes circulating in southern Mozambique prior to vaccine introduction. Genotypes G2 (32.4%), G12 (28.0%), P[4] (41.4%) and P[6] (22.9%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Lineage III strains, on the other hand, are the mostly contemporary G12 strains detected since the mid-2000's and which are now globally prevalent in most continents. This analysis con rms that the genotype G12 strains circulating in these six sub-Saharan African countries (Ethiopia, Kenya, Rwanda, Tanzania, Togo and Zambia) clustered in lineage III with strains circulating all over the world, showing the dominance and biological competitiveness of these strains, which have persisted over the last two decades, in most continents [47][48][49]. Evidence of genetic variation was observed amongst the four G12 lineages in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Lineage III strains, on the other hand, are the mostly contemporary G12 strains detected since the mid-2000's and which are now globally prevalent in most continents. This analysis con rms that the genotype G12 strains circulating in these six sub-Saharan African countries (Ethiopia, Kenya, Rwanda, Tanzania, Togo and Zambia) clustered in lineage III with strains circulating all over the world, showing the dominance and biological competitiveness of these strains, which have persisted over the last two decades, in most continents [47][48][49]. Evidence of genetic variation was observed amongst the four G12 lineages in this study.…”
Section: Discussionsupporting
confidence: 74%
“…As reported before, G12P[6] (28.6%) and G2P[4] (23.1%) were the most predominant genotype combinations at HGM during 2012–2013 [ 24 ]. In 2014 and 2015, G1P[8] and G9P[8] with 84.8% and 73.7%, respectively, were detected at the highest frequencies.…”
Section: Resultsmentioning
confidence: 67%
“…For HGM, a total of 200 genotyped samples corresponded to the pre-vaccine period (2012–2015) and 43 to the post-vaccine period (2016–2019) ( Supplementary Table S3 ). The samples from the pre-vaccine period also included 91 genotyped samples collected at HGM between 2012 and 2013 from a cross-sectional study [ 24 ] to extend the analyses for this particular site ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the VP7-encoding genome segment, Moz308 clusters with the RotaTeq G2P [5] strain, but neither RotaTeq nor Rotarix contain a strain with a G9 or G12 genotype (Figure 1b). However, it is of note that different lineages exist within genotypes and that the VP4-encoding segment of Moz60a and the VP7-encoding segment of Moz308 belong to different lineages than the vaccine strains that they are grouping with in this analysis [36].…”
Section: Selection Of Human Rva Strains From Sub-saharan Africamentioning
confidence: 79%
“…VP8* is genetically diverse and contains four defined antigenic epitopes that are referred to as 8-1 to 8-4, while VP7 contains two epitopes that are referred to as 7-1 and 7-2, whereby the 7-1 epitope can be further divided into 7-1a and 7-1b [12,36,37]. A comparison of the amino acid residues that form the VP8* antigenic epitopes showed that GR10924/99 (G9P [6]) and Moz308 (G2P [4]) differed significantly from the vaccine strains present in Rotarix and RotaTeq (Figure 2a).…”
Section: Sequence Analysis Of Surface-exposed Antigenic Regions Of Humentioning
confidence: 99%